EP1159 Staging system comparison in vulvar squamous-cell cancer. (1st November 2019) - Ferrari, F; Forte, S; Bonetti, E; Sartori, E; Odicino, F
Abstract : Introduction/Background: Currently, there is no agreement regarding the most important prognostic factors of vulvar cancer used to build staging system. The aim of this study is to test the homogeneity, monotonicity and survival classification of FIGO 1988 and 2009. Methodology: We evaluated cases of vulvar squamous-cell carcinoma treated with primary surgery at Spedali Civili of Brescia (Italy) from January 2005 to December 2015. We compared stage distribution of the following poor outcomes of interest between FIGO 1988 and 2009 staging system: local recurrence (LR), nodal recurrence (NR), distant recurrence (DR), multiple recurrence (MR) and disease-specific death (DSD). We used McNemar test to calculate homogeneicity and monotonicy and Kaplan-meier curves with log-rank test to calculate survival differences. Results: We found a total of 123 patients. FIGO 2009 shows a worse homogeneity for poor outcomes compared to FIGO 1988 respectively for stage I with 54 (44%) and 18 (15) events (p=0.0027) and for stage II with 8 (7%) and 44 (36%) events (p=0.00). FIGO 2009 has a better monotonicity compared to FIGO 1988 for stage III with 52 (42%) versus 36 (29%) events (p=0.05), while it has a worse monotonicty in stage IV with 12 (5%) versus 22 (18%) with p=0.02. Survival rates for every stage were compared between FIGO 1988 and 2009 and are as follows: stage I 89.5% versus 89.4% (p=0.89), stage II 83.9% versus 50% (p=0.04), stage III 52.9% versus 38.1% (p=0.07) and stage IV 28.6% versus 0% (p=0.03). Conclusion: FIGO 2009 generally fails to classify poor events when compared to FIGO 1988, however it has a better survival classification. Further prognostic factors should be implemented in future revision of the staging system. Disclosure: Nothing to disclose